The prediction of vapour liquid equilibrium behaviour of propane butane mixture - Zakaria, Zainal; Tee, S. Y. (2005)

(untitled)
This paper is a contribution to the development of mathematical model for the prediction of vapour liquid equilibrium behaviour of propane butane mixture at non-ideal state. The proposed model is based on the generalized virial equation of state and Gamma/Phi formulation. Mathematical modeling, Mathcad is used to numerically solve for fugacity, fugacity coefficient, activity coefficient and vapour-phase composition of propane butane mixture by taking into consideration the effects of temperature and pressure. A temperature range of 263.15K to 313.15K chosen in this modeling is of practicability for propane butane mixture in cylindrical storage. The prediction of vapour liquid equilibrium behaviour for propane butane mixture is illustrated in PxY diagram at different system temperatures. It is clearly shown that solution fugacity coefficient decreases steadily as system temperature and pressure increase. It is also shown that the solution fugacity increases with system temperature and pressure. Activity coefficient of butane in mixture becomes larger as system temperature and pressure increase. Meanwhile, there is insignificant decrease in activity coefficient of propane with temperature and pressure. As system temperature and pressure go higher, vapour-phase composition of propane decreases while for butane, its concentration in vapour phase becomes richer.